(3fXGe GdfbO GdOhdj hGdJLGQI GdNGQLjI ddHdGO GdYQHjI (B/s - (3Ydi, YHO GdefYe GdSjOs; (3GdMHjH, YHO GdQMef s ((3HjQhJ(B: s (3GdeDSSI GdLGeYjI ddOQGSGJ hGdfTQ hGdJhRjY(B, s, 1986)
(3GdCReI GdfbOjI GdOhdjI hGdCReI GdEbJUGOjI GdOhdjI hGdHdOGf GdfGejI(B- (3CKQ GfgjGQ fXGe HQjJhf hhOR (B.s
Keywords: (3GdJLGQI GdNGQLjI(B- (3GdHdGO GdYQHjIs; (3GdYGde GdYQHj(B- (3GdYdGbGJ GdEbJUGOjIs; (3fXGe GdfbO GdOhdjs